Двое под солнцем: роман / Татьяна Тронина - Тронина Татьяна Михайловна (Эксмо, 2022)
Экземпляры: (20230424) / Инвентарный номер: 42549 / Цена: 269.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Т 73 / ГРНТИ: 17 / ББК: 84(2=411.2)6